FDMC: Framework for Decision Making in Cloud for Efficient Resource Management - Alexander Ngenzi; Selvarani R; Suchithra R (Institute of Advanced Engineering and Science, 2017)
An effective resource management is one of the critical success factors for precise virtualization process in cloud computing in presence of dynamic demands of the user. After reviewing the existing research work towards resource management in cloud, it was found that there is still a large scope of enhancement. The existing techniques are found not to completely utilize the potential features of virtual machine in order to perform resource allocation. This paper presents a framework called FDMC or Framework for Decision Making in Cloud that gives better capability for the VMs to perform resource allocation. The contribution of FDMC is a joint operation of VM to ensure faster processing of task and thereby withstand more number of increasing traffic. The study outcome was compared with some of the existing systems to find FDMC excels better performance in the scale of task allocation time, amount of core wasted, amount of storage wasted, and communication cost.